2019
DOI: 10.3311/ppci.14459
|View full text |Cite
|
Sign up to set email alerts
|

Model of Soil-structure Interaction of Objects Resting on Finite Depth Soil Layers for Seismic Design

Abstract: In case of seismic design of structures the deformability and damping of the soil should be considered, which can be performed in several ways. The infinite soil half space can be approximated with the cone model, which gives constant values for the spring stiffnesses and dashpot characteristics, and an additional mass element for rocking motion. To approximate the dynamic impedance function of a soil layer more complex models were also applied. Most of the methods do not take into account the finite dimension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The wavelength L is approximated by the following reasoning. For shallow layers, a quarter-wave is assumed in the soil [23], Fig. 4(a).…”
Section: Assumptions and Basic Hypothesismentioning
confidence: 99%
“…The wavelength L is approximated by the following reasoning. For shallow layers, a quarter-wave is assumed in the soil [23], Fig. 4(a).…”
Section: Assumptions and Basic Hypothesismentioning
confidence: 99%
“…When the undamped (ξ=0), infinitely long constrained beam or bar is loaded by a harmonic edge load at x=0; for ω< ωc the steady-state solution shows no energy dissipation, it behaves like a SDOF system. However, when ω> ωc there is energy dissipation (due to the so called "radiation damping") and the displacement propagates far from the edge [15].…”
Section: Analytical and Numerical Solution Of Long Platesmentioning
confidence: 99%
“…Therefore, small-scale tests, numerical evaluations, and real-scale tests have shown that rocking foundations' application can be considered an efficient approach to reducing damage to structures. Pap and Kollár [29] conducted a study to model of soil-structure interaction of objects resting on finite depth soil layer using a simplified model, and their finding showed that in modeling the soil-foundation interaction by finite element method, the effects of soil should be taken into account by their introduced model.…”
Section: Introductionmentioning
confidence: 99%